ЗИЙРЕК ТАЛАБАЛАРДЫҢ ӨЗ БЕТИНШЕ ЖУМЫС АЛЫП БАРЫЎЫН ШӨЛКЕМЛЕСТИРИЎ УСЫЛЛАРЫ - Қурбанбаева, Д. (ILIM hám JÁMIYET, 2017)
The article is devoted to the issues of organizing the independent work of gifted students in Pedagogics, and using innovative pedagogical technologies. The authors of the article give useful recommendations how to organize effectively the work with gifted students.